Blood Flow Restriction Training Reduces Blood Pressure During Exercise Without Affecting Metaboreflex Activity - Crisafulli, Antonio; de Farias, Rafael Riera; Farinatti, Paulo; Lopes, Karynne Grutter; Milia, Raffaele; Sainas, Gianmarco; Pinna, Virginia; Palazzolo, Girolamo; Doneddu, Azzurra; Magnani, Sara; Mulliri, Gabriele; Roberto, Silvana; et al. (Frontiers in Physiology, 2018)
Objective: Blood flow restriction training (BFRT) has been proposed to induce muscle hypertrophy, but its safety remains controversial as it may increase mean arterial pressure (MAP) due to muscle metaboreflex activation. However, BFR training also causes metabolite accumulation that may desensitize type III and IV nerve endings, which trigger muscle metaboreflex. Then, we hypothesized that a period of BFR training would result in blunted hemodynamic activation during muscle metaboreflex. Methods: 17 young healthy males aged 18 to 25 yrs enrolled in this study. Hemodynamic responses during muscle metaboreflex were assessed by means of postexercise muscle ischemia (PEMI) at baseline (T0) and after one month (T1) of dynamic BFRT. BFRT consisted of 3-min rhythmic handgrip exercise applied 3 days/week (30 contractions per minute at 30% of maximum voluntary contraction) in the dominant arm. On the first week, the occlusion was set at 75% of resting systolic blood pressure (always obtained after 3 min of resting) and increased 25% every week, until reaching 150% of resting systolic pressure at week four. Hemodynamic measurements were assessed by means of impedance cardiography. Results: BFRT reduced MAP during handgrip exercise (T1: 96.3±8.3 mmHg vs. T0: 102.0±9.53 mmHg, p=0.012). However, no significant time effect was detected for MAP during the metaboreflex activation (P>0.05). Additionally, none of the observed hemodynamic outcomes, including systemic vascular resistance, showed significant difference between T0 and T1 during the metaboreflex activation (P>0.05). Conclusion: BFRT reduced blood pressure during handgrip exercise, thereby suggesting a potential hypotensive effect of this modality of training. However, MAP reduction during handgrip seemed not to be provoked by lowered metaboreflex activity.